Influence of Age, Gender and Body Mass Index on Intravenous Pharmacokinetics of Buprenorphine in Children Undergoing Orthopedic Surgery - Liliana Rivera-Espinosa; Eréndira Vicencio-Rosas; Carmen Flores-Pérez; Janett Flores-Pérez; Ismael Lares-Asseff; Jesús Alonso Gándara Mireles; Edelmira Solorio-López; Juan Luis Chávez-Pacheco (SAGE Publishing, 2024)
Background Buprenorphine (BPN) is a widely used analgesic in the pediatric population, although there are few studies on the pharmacokinetics and pharmacodynamics of this drug. Objective The objective was to characterize the pharmacokinetics of BPN after intravenous administration and analyze the effect of age, gender, weight, height, body mass index (BMI), and drug-drug interactions as covariates. Methods Ninety-nine children (2-10 years), who underwent orthopedic surgery under regional, general, or combined anesthesia were included. Patients evaluated according to the American Society of Anesthesiologists Physical Status Classification, who received intravenous BPN 2 μg/kg were enrolled. Blood was collected from 1-240 min. Drug plasma concentrations were determined by LC-MS/MS. Population pharmacokinetic parameters were obtained with Monolix 2021R1 software. Pearson's correlation and/or ANOVA were used for statistical analysis. Results Age was associated with changes in clearance and central compartment volume and the female gender was associated with lower intercompartmental clearance, while BMI modified clearance, central and peripheral compartment volume. Concomitant administration of BPN with fentanyl and dexamethasone produced decreases in clearance. Conclusions The covariates of sex, age, and BMI are directly related to the increase or decrease in BPN pharmacokinetic parameters.